Keragaman Genetik Gen Pvk12 pada Isolat Plasmodium Vivax sebagai Penanda Resistensi terhadap Artemisinin - Putri Dwi Romodhyanti; Chairil Anwar; Dwi Handayani; Dalilah Dalilah; Gita Dwi Prasasti; Iche Andriyani Liberty (Syntax Corporation, 2022)
Malaria is a significant global health problem with a substantial disease burden worldwide. Malaria is caused by the Plasmodium parasite which is transmitted to humans through the bite of Anopheles. There are five species of Plasmodium that cause malaria in humans, it is known that P. falciparum and P. vivax account for the majority of malaria cases. Currently, the main treatment for malaria is artemisinin-based combination therapy (ACT) in most malaria endemic countries and is effective in reducing malaria-related mortality and morbidity globally. However, the emergence of artemisinin-resistant P. falciparum parasites in the propeller domain of the PfK13 gene from Southeast Asian isolates raises awareness of the emergence of resistance in P. vivax. Mutations in the propeller domain of the PfK13 gene are closely related to the degree of delay in parasite clearance in patients treated with antiretroviral therapy so that the identification of vivax malaria resistance markers is focused on the PvK12 gene or the PfK13 gene from P. falciparum. This study used descriptive analysis with a quantitative approach by reviewing 10 articles that were selected according to the criteria. Article searches were carried out through the ScienceDirect, PubMed, Google Scholar, and Directory of Open Access Journal (DOAJ) sites with the keywords: artemisinin resistance, P. vivax and PvK12 genes. There are 7 articles which show very limited polymorphism in the propeller domain of the PvK12 gene in P. vivax. While the other 3 articles did not show any PvK12 gene polymorphisms. Continued monitoring of clinical drug efficacy and molecular markers is necessary to alert against vivax malaria drug resistance and achieve malaria elimination status